If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -7) = 2(x + -8) Reorder the terms: 3(-7 + x) = 2(x + -8) (-7 * 3 + x * 3) = 2(x + -8) (-21 + 3x) = 2(x + -8) Reorder the terms: -21 + 3x = 2(-8 + x) -21 + 3x = (-8 * 2 + x * 2) -21 + 3x = (-16 + 2x) Solving -21 + 3x = -16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -21 + 3x + -2x = -16 + 2x + -2x Combine like terms: 3x + -2x = 1x -21 + 1x = -16 + 2x + -2x Combine like terms: 2x + -2x = 0 -21 + 1x = -16 + 0 -21 + 1x = -16 Add '21' to each side of the equation. -21 + 21 + 1x = -16 + 21 Combine like terms: -21 + 21 = 0 0 + 1x = -16 + 21 1x = -16 + 21 Combine like terms: -16 + 21 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| 3+30x=15x+6 | | 2-x/45 | | 6a+6=2a-6 | | 73-3x=10-10x | | 2x*2-9x-18=0 | | 2x+36=12x-198 | | 9x+y=33 | | x^5-4x^4+3x^3-3x^2+2x+13=0 | | 0=5x^2-20x+17 | | (5y+7)(6+y)=0 | | 2x*-9x-18=0 | | (3+a+b)(3+a+b)= | | 10m+8-4m-4= | | 2x-17=10x+3 | | 4(3y+2)+3(2z-3)=61 | | 12=2(x+4) | | x^4-5x^3+8x^2-11x+13=0 | | (2x+2)-(2x-1)= | | 9n+1=6n+13 | | x^2-14=15x | | x+(x*2)=450 | | x^2+x-2=2 | | (X+4+5)*(x+5)=480 | | 6*(a-43)-36=18 | | 6x(a-43)-36=18 | | (y-4)/2=(2-y)/3 | | 4(22+13)=28 | | 4x-5=1/3 | | 7-4x/53 | | 3x+21=66 | | 2y-9*2= | | 2x-5=x-(3x+4) |